The Effectiveness of Developing Galactic Spin Media in Introducing Textures at Putra Harapan Wiyung Kindergarten - Presdiana, Merya Nancy Jihan; Ningrum, Mallevi Agustin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Different types of textures—such as rough, smooth, soft, or hard—can provide varying sensory stimulation for children. Texture influences the way children interact with objects around them, as well as their learning experiences and cognitive development. Based on this premise, this study aims to determine the effectiveness of the Galactic Spin media at Putra Harapan Wiyung Kindergarten. This research is based on R&D using the ADDIE model. The results indicate that the application of Galactic Spin media for texture indicators among children aged 5–6 years at Putra Harapan Wiyung Kindergarten was categorized as effective, as the significance values were less than 0.05, with details showing a significance value of 0.000 for class A1 and 0.001 for class A2.